Desenvolvimento e validação de metodologias analíticas para o controle de qualidade do radiofármaco Psma - 1007 (18f) para utilização em Pet/Ct - Werlang, Frederico Guevara (2020)
Radiopharmaceuticals are indispensable to assist in the diagnosis and therapeutic management of patients affected by prostate cancer. Nuclear medicine (NM) uses these drugs in imaging tests such as positron emission tomography (PET/CT) and single photon emission computed tomography (SPECT) for responses to morphofunctional images that are possible to evaluate and quantify pathological processes in a non-invasive manner. A radiopharmaceutical of great importance in this treatment is prostatic specific membrane antigen (PSMA-1007 (18F)), which can identify tiny lesions and metastatic tumours. The radioisotope - 18F - was produced by a cyclotron and a sample of the referred radiopharmaceutical was through nucleophilic substitution. Thus, this work aimed at the validation of analytical methodologies for the radiopharmaceutical PSMA-1007 (18F), specific for use in PET / CT. The validation of analytical methodologies is a guarantee for quality control that all the analyzes are well performed. Radiochemical purity was developed and validated by high performance liquid chromatography (HPLC) with a C18 column of 150 x 4.6 mm and 3.0 µm. The residual solvents monitored are ethanol and dimethyl sulfoxide (DMSO) in a chromatographic run of approximately 22 minutes. All methodologies for microbiological control are available to perform the analyzes, with the control of the production sterilization process carried out by determining the bubble point. Stability test guarantees the stability of the product and the definition of its shelf life of ten hours, in addition to ensuring the absence of radiolysis in the filling process. The half-life and radionuclide purityassay show that the radioisotope Fluor 18 (18F) was adequately used in the production.